The lncRNA HOTAIRM1 regulates the degradation of PML-RARA oncoprotein and myeloid cell differentiation by enhancing the autophagy pathway - Chen, Zhen-Hua; Wang, Wen-Tao; Huang, Wei; Fang, Ke; Sun, Yu-Meng; Liu, Shu-Rong; Luo, Xue-Qun; Chen, Yue-Qin (Cell death and differentiation, 2017)
Increasing evidence has indicated that long noncoding RNAs (lncRNAs) are of great importance in different cell contexts. However, only a very small number of lncRNAs have been experimentally validated and functionally annotated during human hematopoiesis. Here, we report an lncRNA, HOTAIRM1, which is associated with myeloid differentiation and has pivotal roles in the degradation of oncoprotein PML-RARA and in myeloid cell differentiation by regulating autophagy pathways. We first revealed that HOTAIRM1 has different variants that are expressed at different levels in cells and that the expression pattern of HOTAIRM1 is closely related to that of the PML-RARA oncoprotein in acute promyelocytic leukemia (APL) patients. We further revealed that the downregulation of HOTAIRM1 could inhibit all-trans retinoic acid (ATRA) -induced degradation of PML-RARA in APL cells and repress the process of differentiation from promyelocytic to granulocytic cells. More importantly, we found that HOTAIRM1 regulates autophagy and that autophagosome formation was inhibited when HOTAIRM1 expression was reduced in the cells. Finally, through the use of a dual luciferase activity assay, AGO2 RNA immunoprecipitation and RNA pull-down, HOTAIRM1 was revealed to act as a microRNA sponge in a pathway that included miR-20a/106b, miR-125b and their targets ULK1, E2F1 and DRAM2. We constructed a human APL-ascites SCID mouse model to validate the function of HOTAIRM1 and its regulatory pathway in vivo . This is the first report showing that a lncRNAs regulates autophagy and the degradation of the PML-RARA oncoprotein during the process of myeloid cell differentiation blockade, suggesting that lncRNAs may be the potential therapeutic targets for leukemia.